Analisis Kemampuan Berpikir Kreatif Matematis Siswa dalam Menyelesaikan Soal Tipe Pisa Ditinjau dari Gaya Kognitif Field Independent - Rinaldi, Raja Muhammad Fadli; Elvi, Mariyanti; Susanti (Papanda, 2025)
The purpose of this study is to analyze how students’ mathematical creative thinking skills in solving PISA-type problems are viewed from the perspective of the field-independent cognitive style. This research employs a descriptive method using a qualitative research approach. The subjects of the study were taken from Grade X students of SMA Negeri 4 Tanjungpinang during the even semester of the 2024/2025 academic year. The research subjects were selected using purposive sampling, with one of the criteria being that the students possess a field-independent cognitive style and complete a creative thinking ability test. The instruments used in this study include a cognitive style test, a creative thinking ability test, and interview guidelines. The data analysis technique applied was qualitative analysis through data reduction, data presentation, and conclusion drawing. Students with a field-independent cognitive style were able to meet at least the originality indicator, which is categorized at the moderately creative level. This is due to the tendency of students with a field-independent cognitive style to focus on the most correct answer and the easiest problem-solving strategy, while still being able to think independently and generate strategies based on their own reasoning.